Perlindungan Hukum Akibat Itikad Buruk Perusahaan Dalam Menjalankan Usaha Asuransi Atas Polis Asuransi Jiwa - Harahap, Herlina Hanum (Universitas Islam Sumatera Utara, 2023)
The principle of utmost good faith is the most important principle in a life insurance agreement. The application of this principle in the practice of life insurance, among others, occurs when the insured completes the insurance request form. This research uses a descriptive method through a normative approach (legal research), namely an approach to problems, carried out by examining various legal aspects in terms of applicable regulations. The results of the study show that the form of legal protection provided to consumers in the life insurance business in Indonesia is the principle of utmost good faith adhered to in the life insurance business, which is an act of accurately informing all information that is requested or not requested by the insurance company regarding something. to be insured or the insured object/interest. Forms of bad faith from life insurance companies on life insurance policies related to their obligations in running a life insurance business are that the insurer often does not want to make payments on life insurance claims. As for the form of legal action taken in resolving consumer disputes over life insurance policies in Indonesia through (three) stages of dispute resolution and in this case there is no appeal against the decision of the district court which decided objections to the decision of the Consumer Dispute Settlement Agency, but was immediately appealed to the Court great . Keywords: Legal Protection, Bad Faith, Life Insurance.